The Introduction to Python Programming Language for Students at Mtsn 4 Pandeglang School - M. BADRU TAMAM; masduki asbari (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
The Industrial Era 4.0 brings Indonesians to a technological mindset that covers various aspects of life. Technology is now reopened to luxury things so that people cannot be separated from the rise of technological facilities. In preparation for entering the industrial era 5.0, there is no doubt that information retrieval is strongly supported and facilitated by various technology-based devices and applications. Information that is currently an important basic material in forming concrete data makes information important in various aspects of life. Based on the saying